Pengembangan Instrumen Penilaian Afektif pada Mata Pelajaran PAI - Fuad Hasim (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
Education is carried out to explore and then develop various competencies that already exist in each student, these competencies include abilities in the scientific field, attitudes and skills. These three competencies should be developed optimally and in a balanced way both in the learning process in class and in the implementation of assessments/evaluations. Facts on the ground show that affective domain assessment tends to be more difficult to implement and develop, in contrast to the cognitive and psychomotor competencies that are very commonly carried out by educators. Therefore, this study aims to help find solutions to the problems of affective assessment which have tended to be stagnant. This research includes library research using a qualitative descriptive approach and using Permendikbud Number 23 of 2016 concerning Assessment Standards and Presidential Regulation of the Republic of Indonesia Number 87 of 2017 concerning Strengthening Character Education as the primary data source and supported by several other supporting literature. The results of the study indicate that the affective domain assessment of students must be carried out thoroughly both when they are in the school, family or community environment around where they live. This assessment is carried out by observing the behavior of students and the observed behavior is the values of character education that have been stipulated in Presidential Decree Number 87 of 2017 concerning Strengthening Character Education. These values include religious, honest, tolerant, disciplined, hard working, creative, independent, democratic, curiosity, national spirit, love of the motherland, respect for achievement, communicative, love of peace, love to read, care for the environment, care for social And Responsibility. These values are observed and then converted into students' final scores on the affective/attitude aspects of students which are outlined in the form of Very Good, Good, Enough and Less values